Systematic review and meta-analysis of the effectiveness of continuous glucose monitoring (CGM) on glucose control in diabetes - Poolsup, Nalinee (BioMed Central, 2013)
Diabetes mellitus is a chronic disease that necessitates continuing treatment and patient self-care education. Monitoring of blood glucose to near normal level without hypoglycemia becomes a challenge in the management of diabetes. Although self monitoring of blood glucose (SMBG) can provide daily monitoring of blood glucose level and help to adjust therapy, it cannot detect hypoglycemic unawareness and nocturnal hypoglycemia which occurred mostly in T1DM pediatrics. Continuous glucose monitoring (CGM) offers continuous glucose data every 5 minutes to adjust insulin therapy especially for T1DM patients and to monitor lifestyle intervention especially for T2DM patients by care providers or even patients themselves. The main objective of this study was to assess the effects of continuous glucose monitoring (CGM) on glycemic control in Type 1 diabetic pediatrics and Type 2 diabetic adults by collecting randomized controlled trials from MEDLINE (pubmed), SCOPUS, CINAHL, Web of Science and The Cochrane Library up to May 2013 and historical search through the reference lists of relevant articles. There are two types of CGM device: real-time CGM and retrospective CGM and both types of the device were included in the analysis. In T1DM pediatrics, CGM use was no more effective than SMBG in reducing HbA1c [mean difference – 0.13% (95% CI -0.38% to 0.11%,]. This effect was independent of HbA1c level at baseline. Subgroup analysis indicated that retrospective CGM was not superior to SMBG [mean difference -0.05% (95% CI -0.46% to 0.35%)]. In contrast, real-time CGM revealed better effect in lowering HbA1c level compared with SMBG [mean difference -0.18% (95% CI -0.35% to -0.02%, p = 0.02)]. In T2DM adults, significant reduction in HbA1c level was detected with CGM compared with SMBG [mean difference – 0.31% (95% CI -0.6% to -0.02%, p = 0.04)]. This systematic review and meta-analysis suggested that real-time CGM can be more effective than SMBG in T1DM pediatrics, though retrospective CGM was not. CGM provided better glycemic control in T2DM adults compared with SMBG.